Phenotypic characterization and diversity of Nepalese garlic (Allium sativum L.) landraces - Shrestha, Deepa Singh; Chaudhary, Jeet Narayan; Ghimire, Krishna Hari; Shrestha, Jiban (Journal of Agriculture and Natural Resources, 2022)
A total 37 garlic landraces collection from Nepal Genebank were characterized using phenotypic trait maps or agro morphological markers at National Agriculture Genetic Resources Centre (Genebank), Khumaltar, Lalitpur, Nepal during 2017 using quantitative and qualitative traits. Shannon and Weaver diversity index (H’) analysis revealed significant intra landrace diversity for both quantitative and qualitative traits. Nine principal components contributed 100 % to the cumulative variance and the first three principle components with Eigen value >1 accounted for 69.9 % of the entire variability.The cluster analysis grouped the 37 accessions into five distinct group. The Accession CO4816 from cluster 5 were superior in terms of yield attributing characters such as number of cloves/bulb, weight of cloves and yield but found to be shorter is plant height. Pearson correlation analysis among eight quantitative traits showed highly significant positive correlation between leaf length and leaf width, leaf length and shaft length, leaf length and yield, weight of cloves and yield. The high yield is associated with leaf length, leaf width, weight of cloves and number of cloves. The frequency distribution for disease (Cercospora leafspot and Alternaria porii) occurrence were very low in 78 % of the accessions.